Factors Related to Utilization of Maternal Health Service Facilities in the Working Area of Mangili Public Health Center - Desi Hunggu Urang; Erny Erawati Pua Upa; Yoseph Kenjam (Lontar : Journal of Community Health, 2021)
Maternal mortality ratio (MMR) is one of the problems that has made the focus of the Indonesian government to make policies in the health sector. The main factor causing high MMR is unsafe delivery, either not assisted by health workers or was not in health facilities. This study aimed to analyze the correlation between knowledge, attitudes, husband/family support, and the use of health service facilities in the working area of the Mangili Community Health Center. This cross-sectional study consisted of 104 respondents selected using a cluster sampling technique. The data were analyzed univariably and bivariably using the Chi-square test. The results showed that knowledge (p = 0.040), attitude (p = 0.043), and husband/family support (p = 0.027) are related to the use of health service facilities. Health workers, especially midwives, are expected to monitor and do home visits and provide intensive education to pregnant women and their families to ensure childbirth in health care facilities. On the other hand, the role of the husband/family needs to be optimized to support the mother through motivation, attention, and assistance during pregnancy examinations until delivery.